Identification of Auxochrome Units with a Site for the Attachment of Recognition Moiety for Detection of Biomolecules - Das, Samarpita (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Pharmaceutical Engineering